Diagnostic Value of Endotoxin Activity for Acute Postoperative Complications: A Study in Major Abdominal Surgery Patients - Hye Sung Kim; Gyeo Ra Lee; Eun Young Kim (Biomedicines)
Background/Objectives: Endotoxin, a component of lipopolysaccharide (LPS) from bacteria, disrupts the immune system, potentially leading to multiorgan failure. Unlike previous studies, we enrolled patients with mild clinical conditions after major abdominal surgery and assessed the predictive value of endotoxin activity (EA) levels for acute complications which occur within 7 days postoperatively. Also, the differential diagnostic value of EA was assessed in a subgroup of patients with abnormal liver function during the immediate postoperative period. Methods: Patients admitted to the surgical ICU of our institution following elective abdominal surgery were enrolled. Participants were classified into low/high postoperative EA groups based on EA cutoff values for predicting complications. Additionally, participants were categorized based on liver function assessed at ICU admission using total bilirubin (TB) levels. Abnormal liver function was defined as a TB level > 1.2 mg/dL. Results: 86 patients were analyzed. The EA cutoff for postoperative complications was 0.485, with 49 patients (57%) categorized in the low EA group (EA levels < 0.485) and 37 patients (43%) in the high EA group (EA levels ≥ 0.485). The high EA group experienced statistically worse outcomes, including longer ICU stays and higher mortality rates. Logistic regression analysis confirmed that EA levels and SOFA scores were significant predictors of postoperative complications. For patients with elevated TB, the EA cutoff value for postoperative complications was 0.515, which is higher than those obtained for the total patient cohort. Conclusions: EA level is a viable surveillance tool for detecting postoperative complications in the acute period among ICU patients undergoing major abdominal surgery, and must be interpreted carefully considering the patient’s liver function.